Beyond BMI: A Patient-Centered Approach to Discussing Obesity - Sharon Anderson; Enjoli Benitez; Edith Gonzalez-Godinez; Yatri Desai; Nickveer Heer; Jordan White (Methodist DeBakey Cardiovascular Journal)
This Points to Remember column outlines an approach to initiating the discussion of obesity with a patient in the clinical setting. Written by faculty and residents of the Houston Methodist Family Medicine Residency Program, these points can help physicians develop a patient-centered approach to broaching the discussion of weight management that fosters an open dialogue and works to reduce weight stigma and biases surrounding obesity.